2015
DOI: 10.1002/mde.2732
|View full text |Cite
|
Sign up to set email alerts
|

Location Choice and Contract Bargaining

Abstract: We study how managerial bargaining power affects outcomes and payoffs in a Hotelling‐type duopoly framework with restricted and unrestricted locations. We show that bargaining power only affects the distribution of the surplus between owners and managers but does not affect the locations, prices, managerial incentives, and consumer welfare. This is in stark contrast to van Witteloostuijn et al. (2007) and related contributions where bargaining power has real effects. We argue that the difference between our ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As known,Eaton and Grossman (1986) have shown that the optimal choice for governments is a tax (instead of a subsidy) in the case of price (instead of quantity) competition. In such a case, the policy intervention is welfare superior (for producing countries) to free trade.11 For the sake of clarity, we recall here that the Brander and Spencer's result always holds true also under the preceding extensions to the managerial delegation surveyed in the Introduction and thus only in the present model with owner-manager bargaining the presence of managerial delegation may modify such results.12 For instance, this alternative view of managerial contracts has been recently investigated byKopel, Pezzino, and Ressi (2015) in a location model framework.13 The expressions for q(s i , s j ), π(s i , s j ), and SW(s i , s j ) are too long and omitted here for brevity. 14 The equilibrium outcomes under free trade are easily obtained by setting s i = s j = 0 in Equations A.7-A.13.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…As known,Eaton and Grossman (1986) have shown that the optimal choice for governments is a tax (instead of a subsidy) in the case of price (instead of quantity) competition. In such a case, the policy intervention is welfare superior (for producing countries) to free trade.11 For the sake of clarity, we recall here that the Brander and Spencer's result always holds true also under the preceding extensions to the managerial delegation surveyed in the Introduction and thus only in the present model with owner-manager bargaining the presence of managerial delegation may modify such results.12 For instance, this alternative view of managerial contracts has been recently investigated byKopel, Pezzino, and Ressi (2015) in a location model framework.13 The expressions for q(s i , s j ), π(s i , s j ), and SW(s i , s j ) are too long and omitted here for brevity. 14 The equilibrium outcomes under free trade are easily obtained by setting s i = s j = 0 in Equations A.7-A.13.…”
mentioning
confidence: 72%
“…For instance, this alternative view of managerial contracts has been recently investigated by Kopel, Pezzino, and Ressi () in a location model framework.…”
mentioning
confidence: 99%